MEMBANGUN LITERASI TAKDIR DI KALANGAN GENERASI MILENIAL : (ANALISIS ISI ATAS KAJIAN USTADZ HANAN ATTAKI DI SAMARINDA) - S. Dinar Annisa Abdullah (STAI DI AL-HIKMAH, 2025)
This study examines how the Islamic missionary message about the concept of destiny is constructed by Ustadz Hanan Attaki in his lecture entitled